2015
DOI: 10.1097/md.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Symptomatic Vertebral Fractures Among Newly Diagnosed Autoimmune Diseases Initiating Glucocorticoid Therapy

Abstract: Few data are available regarding vertebral fracture risk in patients treated with corticosteroids including patients with interstitial lung disease (ILD). The aim of the present study was to identify risk factors for symptomatic vertebral fracture analyzed in patients with newly diagnosed autoimmune diseases.This was an observational cohort study conducted in the National Hospital Organization-EBM study group from 2006 to 2008. The study subjects were autoimmune disease patients who were newly treated with glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…6 One of the most possible side effects of the usage of glucocorticoids is the trabecular bone mass loss. 11,28 Back pain at different intensities is the main presenting symptom in all patients of G-OVFs. Mild-to-moderate degree of pain in cases of acute vertebral osteoporotic fracture can be relieved by bed rest, bracing, analgesics, anti-osteoporotic drugs (bisphosphonates or denosumab), and anabolic drugs as tripartite (Forteo); 23,38 however, advanced cases with compression fractures mostly need intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 One of the most possible side effects of the usage of glucocorticoids is the trabecular bone mass loss. 11,28 Back pain at different intensities is the main presenting symptom in all patients of G-OVFs. Mild-to-moderate degree of pain in cases of acute vertebral osteoporotic fracture can be relieved by bed rest, bracing, analgesics, anti-osteoporotic drugs (bisphosphonates or denosumab), and anabolic drugs as tripartite (Forteo); 23,38 however, advanced cases with compression fractures mostly need intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Koch et al 23 and others 9,15 reported that patients with G-OVFs experience levels of pain relief and development of new fractures after PV similar to those with primary osteoporotic vertebral fractures. There was another study 28 stating that adverse effects on bone are mainly due to underlying autoimmune or inflammatory disorders. The previous results support the use of PV to treat OVFs unresponsive to conservative management in patients receiving long-term corticosteroid therapy.…”
Section: Cement Leakmentioning
confidence: 99%
“…In the literature, some reported that chronic obstructive pulmonary disease, autoimmune disease, collagen vascular disease including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjogren's syndrome (SS), systemic sclerosis (SSc)/mixed connective tissue disease (MCTD), polymyositis/dermatomyositis (PM/DM), and microscopic polyangiitis are related to the risk of vertebral fractures. 38 , 39 , 40 , 41 But those results are also related to long time steroid usage. In our study, the result showed that those connective tissue disease and chronic lung disease were not associated with repeated PVP or kyphoplasty.…”
Section: Discussionmentioning
confidence: 99%